Current Clinical Indications for Plerixafor - Fruehauf, Stefan (S. Karger GmbH, 2013)
Autologous and allogeneic hematopoietic stem cell (HSC) transplantation are considered the standard of care for many malignancies including lymphoma, multiple myeloma, and some leukemias. In many cases, mobilized peripheral blood has become the preferred source for HSCs. Plerixafor, an inhibitor of the interaction between CX chemokine receptor 4 (CXCR4) and stromal derived factor-1 alpha (SDF-1), has been evaluated in clinical trials and approved by the FDA and EMA. This agent has very modest toxicity and appears to be quite potent at HSC mobilization. Current clinical indications for the use of plerixafor are the subject of this review.